Instituiç\~oes e investimentos privados em infraestrutura nas economias emergentes - Katia Rocha; Ajax Reynaldo Bello Moreira; Gabriel Godofredo Fiuza de Bragança (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The objective of this study is to analyze the determinants of private investment, especially private participation in infrastructure, focusing on the institutional quality of emerging economies. The emerging economies analyzed (Argentina, Brazil, China, Chile, Colombia, India, Indonesia, Malaysia, Mexico, Paraguay, Peru, Philippines, Russia, South Africa, Turkey, Ukraine, Uruguay and Venezuela) accounted for approximately 80% of the EMBIPLUS index and 60% of the EMBIGLOBAL index, reference indexes of the J.P. Morgan bank correspond in August 2016. The results show that most of the institutional variables analyzed, in particular, economic freedom and regulatory quality, actually explain the number of projects and the investment figure with private participation in infrastructure for the group of emerging economies analyzed in the period 1990-2015 even controlling for liquidity and global risk shocks.
Keywords: G18; F3; G1; 330; infrastructure investments; emerging economies; institutional governance